The path towards progress: a critical review to advance the science of the female and male athlete triad and relative energy deficiency in sport - De Souza, M. J.; Strock, N . C. A.; Ricker, E. A.; Koltun, K. J.; Barrack, M.; Joy, E.; Nattiv, A.; Hutchinson, M.; Misra, M.; Williams, N. I. (Sports Medicine, 2022)
Energy status plays a key role in the health of athletes and exercising individuals. Energy deficiency/low energy availability (EA), referring to a state in which insufficient energy intake and/or excessive exercise energy expenditure has resulted in compensatory metabolic adaptations to conserve fuel, can affect numerous physiological systems in women and men. The Female Athlete Triad, Male Athlete Triad, and Relative Energy Deficiency in Sport (RED-S) models conceptualize the effects of energy deficiency in athletes, and each model has strengths and limitations. For instance, the Female Athlete Triad model depicts relationships between low EA, reproductive, and bone health, underpinning decades of experimental evidence, but may be perceived as limited in scope, while the more recent RED-S model proposes a wider range of potential health effects of low EA, though many model components require more robust scientific justification. This critical review summarizes current evidence regarding the effects of energy deficiency on athlete health by addressing the quality of the underlying science, the strengths and limitations of each model, and highlighting areas where future research is needed to advance the field. With the health and wellness of athletes and exercising individuals as the overarching priority, we conclude with specific steps that will help focus future research on the Female and Male Athlete Triad and RED-S, and encourage all researchers, clinicians, and practitioners to collaborate to support the common goal of promoting the highest quality science and evidence-based medicine in pursuit of the advancement of athletes` health, well-being, and performance.